Estudio de factibilidad para crear una empresa especializada en servicios logísticos de carga y descarga de mercancías en la ciudad de Pereira. (2015)
Operations Logistics RISARALDA SAS is a company focused to provide a quality service for upload, download and storage of goods, with appropriate staff for this work, where after various studies involving a feasibility project it can be said that it is a necessary service in the small and medium-sized enterprises, which are the target market you want to that point. The idea of proof of feasibility that developed during this work, is to give an added value to what today is commonly known as "cotero", which is intended to provide guarantees to small and medium-sized entrepreneurs that their merchandise will be handled properly, with the quality standards necessary, with qualified staff trained in work of load Download and storage of goods. It will be a company legally constituted with all provisions required by law for such organizations, it will also have facilities for proper operation. This staff that carries out the operational work of loading, unloading and storage will have all their benefits Bill, also with elements of safety appropriate for the work they do, aspects that are not seen in the various guilds of "loaders", that currently exist.